Remote Magnetometry With Mesospheric Sodium Based on Gated Photon Counting. Issue 9 (10th September 2019) - Fan, T.; Yang, X.; Dong, J.; Zhang, L.; Cui, S.; Qian, J.; Dong, R.; Deng, K.; Zhou, T.; Wei, K.; Feng, Y.; Chen, W.
Abstract: Remote detection of geomagnetic fields in the mesosphere would provide a powerful tool for mapping and interpreting Earth's lithospheric magnetic fields, monitoring magnetic disturbances in conjunction with the aurora, and making long‐term measurements of ionospheric currents at polar regions. Based on gated photon counting and direct frequency sweep, a remote magnetometry scheme with precession of mesospheric sodium was demonstrated. The technique of gated photon counting has an advantage in background light suppression and has the potential to achieve altitude‐resolved magnetic field measurements with an optimized laser source. An intensity‐modulated laser beam was utilized to optically pump sodium atoms in the mesopause, and a ground‐based telescope collects fluorescent echoes to infer the magnetic field. The experiment was carried out at Lijiang observatory where we validated this technique and measured the geomagnetic field with a sensitivity of 849 nT/Hz 1/2, which can be improved through further optimization. Key Points: Based on gated photon counting and direct frequency sweep, a ground‐based magnetometry scheme with precession of mesospheric sodium was demonstrated We measured the magnetic field in the mesosphere with an accuracy level of 849 nT/Hz 1/2, which can be improved through further optimization The technique of gated photon counting has the potential to achieve altitude‐resolved magnetic field measurements